Characteristics of Privatization: Evidence from Developed, Less-Developed and Former Communist Countries - De Castro, Julio O.; Uhlenbruck, Klaus (Journal of International Business Studies, 1997)
A privatization wave has swept the world, starting in the U.K. in the early 1980s and then progressing to other developed and less-developed nations. This study examines how the country characteristics for the formerly state-owned enterprises relate to the nature of the privatization deal and the strategy of the acquiring firm. In particular, this paper examines how country characteristics affect government privatization policies and, in turn, firm strategy. Results indicate that there are differences with respect to the characteristics of privatization and government policies that translate into differences in firm strategy in former communist, less-developed and developed countries.